Online-dating romance scam in Malaysia: an analysis of online conversations between scammers and victims - Azianura Hani Shaari,; Mohammad Rahim Kamaluddin,; Wan Fariza Paizi@Fauzi,; Masnizah Mohd, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The study of online romance scam is still at its infancy in Malaysia, despite the increase in the number of reported cases in this country. This research primarily aims to identify the steps and strategies involved in the online romance scam in Malaysia. Apart from that, it also aims to identify the pattern of deceptive language used in online romance scam in Malaysia through a comprehensive linguistic analysis of actual online conversations between scammers and victims. The empirical investigation of this research focuses on the language strategies used by scammers as a modus operando in deceiving their targets. With the help of the Malaysian Police Department, a database of romance scam cases was gathered and established. From the database, 30 sets of online communication between scammers and 30 Malaysian victims were selected and analysed using content analysis method. One of the aspects involved in data analysis was scammers’ linguistic styles and patterns in manipulating their targets. This was analysed using Brown and Levinson Politeness Model as well as Whitty’s Scammers Persuasive Techniques Model. The findings indicate a common linguistic pattern and style of conversation used by online scammers in persuading and deceiving their victims.